Design of Religious Moderation Education in Muhammadiyah Middle School and Ma'arif NU Middle School Educational Institutions - Umam, Khairul; Karim, Abdul; Abidin, Zainal (Program Studi Pendidikan Agama Islam, 2023)
This study aims to analyze the application of religious moderation education curriculum design in educational institutions, including Mandiri Berbagi and Mandiri Berubah Curriculum Models, collaborative and separate curriculum design, and hidden curriculum design in SMP Muhammadiyah 6 Wuluh and SMP 09 Ma'arif NU Ambulu in Jember. This study used a qualitative approach with the type of case study to describe and analyze the design of religious moderation education in educational institutions. Data collection was conducted by observing the activities of teachers and principals in designing a religious moderation education curriculum. At the same time, interviews were carried out with the principal, subject teacher, and the vice principal of curriculum involved in the design of religious moderation education. Data analysis follows the Miles, Huberman, and Saldana models, including data condensation, data presentation, and inference. Furthermore, the validity of the data was ensured using source and technical triangulation. The findings of this study revealed 1) the application of religious moderation education curriculum with Mandiri Berbagi and Mandiri Berubah Curriculum Models, 2) the design of moderation education curriculum with collaborative model of ISMUBARIS (Islam, to-Muhammadiyah, Arabic and Islamic Cultural History) and a separate model between religious education and the teachings of Nahdatul Ulama, and 3) hidden curriculum on all subjects with the message of Islam wasathiyah and moderate Islamic messages of an-Nahdiya. This research contributes to policymakers, such as the government, the Ministry of Education and Culture, the Ministry of Religion, and all educational institutions, such as junior high schools and MTs, in implementing religious moderation education for application in the curriculum and learning of Islam.